EFFECT OF DIFFERENT STOCKING DENSITY TO GROWTH RATE OF CATFISH (Clarias gariepinus, Burch) CULTURED IN BIOFLOC AND NITROBACTER MEDIA - Puspita, Elfa Verda; Sari, Ratih Purnama (AQUASAINS, 2018)
Catﬁsh is one of the freshwater commodities whose demand continues to increase in Indonesia. Intensive cultivation is done to meet market demand. Intensive cultivation is done by optimizing stocking density. The aim of this research was to know the effect of different density on feed productivity, growth, feed conversion ratio (FCR) and survival of catﬁsh dumbo fry (Clarias gariepinus, Burch) in bioﬂoc and nitrobacter media. This study used a completely randomized design (RAL) with 6 treatments and 3 replications. The test animalsused catﬁsh dumbo (Clarias gariepinus, Burch) with an average weight of 0,6 ± 0,1g and an average length of 4 cm. Catﬁsh dombo seeds are kept in tarpaulin ponds 2 m in diameter with water volume ± 1 m3 for 45 days and feeding 3% of biomass weight. The results showed that the different density of stockingin bioﬂoc and nitrobacter media had increase on productivity, speciﬁc growth rate, feed efﬁciency and no signiﬁcant effect on the survival of catﬁsh dumbo fry.